The Eastern and Western mystic philosophy and allness reflected in Andrei Tarkovsky’s films - Eun Park, Young (Slavia Centralis, 2021)
This article examines Tarkovsky’s works at various levels by understanding his individual work microscopically based upon the Eastern and Western religions and philosophy, and analyzes the influence on Tarkovsky’s view of the world. Tarkovsky’s world view, which includes the oriental and western religions and ideas, was able to identify the connection with various ideas of mystic and spiritual philosophers, including Rudolf Steiner and Georgii Gurdzhiev. Tarkovsky explored the books of Gurdzhiev and Uspensky, who led the revolution in the consciousness of the world by introducing the oriental philosophy and performance system to the Western philosophy. He was also very interested in Rudolf Steiner’s philosophy "spiritual science". The expression of Laozi’s "virtues" or Buddhist philosophy in his films is also a proof that he had made efforts to integrate Eastern philosophy with Western philosophy.